2019
DOI: 10.1292/jvms.18-0679
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein expression in Equine Glandular Gastric Disease (EGGD) induced by phenylbutazone

Abstract: Equine Glandular Gastric Disease (EGGD) is a common disease in sport horses. This disease might be associated with usage of nonsteroidal anti-inflammatory drugs (NSAIDs) for treating inflammatory diseases. Although gastroscopy has been an effective method for diagnosis, but a less invasive, and inexpensive method is preferred. This study used proteomic technology to identify candidate serum proteins that might be used as markers of NSAIDs induced EGGD. Five Thoroughbred horses were given high doses of NSAID, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Many clinical signs have been ascribed to gastric mucosal disease over the years, but surprisingly few studies have investigated these on a large scale. Proposed clinical signs, discussed below, include colic [ 4 , 39 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], weight loss or poor body condition [ 4 , 42 , 51 , 52 , 56 , 57 ], poor coat condition [ 39 ], reduced appetite [ 4 , 39 , 51 , 52 , 56 , 58 ], diarrhea [ 51 ], bruxism [ 51 , 52 ], flehmen response [ 37 ], behavioral changes [ 43 , 52 , 56 , 57 , 59 ] and poor performance [ 14 , 37 , 39 , 52 , 56 , 57 , 60 , 61 , 62 ]. In interpreting the above, it is important to distinguish between ESGD and EGGD as the majority of literature is weighted towards ESGD, and a recent study found no associations between owner-reported clinical signs and EGGD [ 63 ].…”
Section: Clinical Signsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many clinical signs have been ascribed to gastric mucosal disease over the years, but surprisingly few studies have investigated these on a large scale. Proposed clinical signs, discussed below, include colic [ 4 , 39 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], weight loss or poor body condition [ 4 , 42 , 51 , 52 , 56 , 57 ], poor coat condition [ 39 ], reduced appetite [ 4 , 39 , 51 , 52 , 56 , 58 ], diarrhea [ 51 ], bruxism [ 51 , 52 ], flehmen response [ 37 ], behavioral changes [ 43 , 52 , 56 , 57 , 59 ] and poor performance [ 14 , 37 , 39 , 52 , 56 , 57 , 60 , 61 , 62 ]. In interpreting the above, it is important to distinguish between ESGD and EGGD as the majority of literature is weighted towards ESGD, and a recent study found no associations between owner-reported clinical signs and EGGD [ 63 ].…”
Section: Clinical Signsmentioning
confidence: 99%
“…Furthermore, several population-based studies have failed to find NSAID use associated with increased risk of EGGD [ 28 , 30 , 90 ]. At an experimental level, multiple studies have shown the ulcerogenic capacity of NSAIDs at high doses in horses [ 50 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Most of these studies, however, use NSAID doses in excess of what is typically recommended for clinical use [ 98 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomics can be a helpful tool in early diagnosis of various diseases, including EGUS. Ten protein markers for equine squamous gastric disease (ESGD) and 14 for EGGD have been successfully identified through proteomics (Tesena et al 2019). Some of these peptides are biomarkers of oxidative stress, and oxidative stress seems to play an important role in various equine gastrointestinal diseases, including colic (Hajimohammadi et al 2023), EGGD (Banse and Andrews 2019), EGUS (Shawaf et al 2020), and colitis (El-Ashker et al 2012), by causing injury to the gastrointestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%